THE DESIGN OF MULTIMEDIA IN STORYTELLING - Eka Pujiastuti (Universitas PGRI Semarang, 2022)
Learning and teaching a foreign language needs a lot of patience, energy, time, creativity, and competence. The success of the teaching and learning of foreign language skills including English is determined by several factors such as students, teachers, teaching methods, techniques, and instructional Multimedia. English teaching Multimedia is very important for the teacher to help students acquire a new concept of the skills and language competencies. This study made use of the qualitative method. The researcher used Educational Research and Development cycle from Borg and Gall (2007) which is adjusted into five steps, namely (1) research and information gathering, (2) planning, (3) preliminary product development, (4) preliminary field testing, and (5) primary product revision. There are still many fascinating discussions that might be interesting to find out the real situation in the implementation of Multimedia in English language teaching, especially in storytelling. This study which was conducted by the students of SMK Mitra Karya Mandiri Ketanggungan-Brebes is intended to figure out how the use of Multimedia in English language teaching to the first levels. The study employed a case study research design. The researcher collected the literature review, distributed questionnaires to the students, and interviewed one of the English teachers. After collecting the literature review, the researcher first distributed the questionnaires to the students. The respondents to the questionnaires were 30 students. The result of the research shows that digital storytelling can be built up to teach narrative. The purpose of the medium must be communicative and attractive to the students. Equally, for the students, they are interested in using digital storytelling to learn about narrative. Hence, digital storytelling is designed to help students in all competencies, such as reading, speaking, listening, writing, and the vocabulary teaching-learning process.